2020
DOI: 10.31128/ajgp-03-20-5286
|View full text |Cite
|
Sign up to set email alerts
|

Symptom management for patients awaiting joint replacement surgery

Abstract: Background Joint replacement surgery is a highly effective treatment option for patients with severe osteoarthritis (OA) of the hip and knee when other treatments have failed. Unfortunately, as a result of the COVID-19 pandemic, a temporary suspension of non-urgent elective surgery was implemented. Thousands of patients currently awaiting hip and knee replacements have been affected. Many of these patients will present to their general practitioners for symptom management during this interim period. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The distribution in level of evidence was as follows: 14% (n = 4) of articles were level 3, 8 , 10 , 12 , 30 14% (n = 4) were level 4, 13 , 16 , 18 , 31 and 72% (n = 21) of articles were level 5. 1 - 7 , 14 , 15 , 17 , 19 - 29 The majority of studies were categorized as expert opinion/societal guidelines (55%). The most common theme among articles was general management recommendations on the resumption of elective arthroplasty and sports medicine surgery (n = 11 articles).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The distribution in level of evidence was as follows: 14% (n = 4) of articles were level 3, 8 , 10 , 12 , 30 14% (n = 4) were level 4, 13 , 16 , 18 , 31 and 72% (n = 21) of articles were level 5. 1 - 7 , 14 , 15 , 17 , 19 - 29 The majority of studies were categorized as expert opinion/societal guidelines (55%). The most common theme among articles was general management recommendations on the resumption of elective arthroplasty and sports medicine surgery (n = 11 articles).…”
Section: Resultsmentioning
confidence: 99%
“… 13 , 16 Uncontrolled pain leads to increased use of analgesics and opioids, placing patients at increased risk of opioid tolerance and addiction. 12 , 13 , 16 , 29 One institution surveyed patients awaiting elective joint replacement during the COVID-19 pandemic and found that 23.4% of patients reported an increase in dose or frequency of pain medication consumption after being told surgery was delayed, with 21.6% of patients surveyed using opioids to manage their arthritis pain. 31 Less mobility and functional limitations can cause lack of independence during a time of increased social isolation and lead to the development of flexion contractures and loss of muscle mass, making postoperative rehabilitation more difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resources and personnel to monitor and optimize air quality Information on safety issues and use of vitamin D/ other supplements Information on the harm of excess opioid usageBox 2Possible socially supportive protective factors providers can foster in efforts to improve anxiety control, stress, pain control, adherence to selfprotection/management strategies, sleep hygiene, immunity, and depression among isolated older adults with osteoarthritis[32, 44,51,55] …”
mentioning
confidence: 99%